Melioidosis Patient Survival Correlates With Strong IFN-γ Secreting T Cell Responses Against Hcp1 and TssM - Sengyee, Sineenart; Yarasai, Atchara; Janon, Rachan; Morakot, Chumpol; Ottiwet, Orawan; Schmidt, Lindsey K.; West, T. Eoin; Burtnick, Mary N.; Chantratita, Narisara; Brett, Paul J. (Frontiers in Immunology, 2021)
Melioidosis, caused by the Gram-negative bacterium Burkholderia pseudomallei, is a serious infectious disease with diverse clinical manifestations. The morbidity and mortality of melioidosis is high in Southeast Asia and no licensed vaccines currently exist. This study was aimed at evaluating human cellular and humoral immune responses in Thai adults against four melioidosis vaccine candidate antigens. Blood samples from 91 melioidosis patients and 100 healthy donors from northeast Thailand were examined for immune responses against B. pseudomallei Hcp1, AhpC, TssM and LolC using a variety of cellular and humoral immune assays including IFN-γ ELISpot assays, flow cytometry and ELISA. PHA and a CPI peptide pool were also used as control stimuli in the ELISpot assays. Hcp1 and TssM stimulated strong IFN-γ secreting T cell responses in acute melioidosis patients which correlated with survival. High IFN-γ secreting CD4+ T cell responses were observed during acute melioidosis. Interestingly, while T cell responses of melioidosis patients against the CPI peptide pool were low at the time of enrollment, the levels increased to the same as in healthy donors by day 28. Although high IgG levels against Hcp1 and AhpC were detected in acute melioidosis patients, no significant differences between survivors and non-survivors were observed. Collectively, these studies help to further our understanding of immunity against disease following natural exposure of humans to B. pseudomallei as well as provide important insights for the selection of candidate antigens for use in the development of safe and effective melioidosis subunit vaccines.